f(n) = 1st term - common difference (n - 1)
The operation is subtraction because the sequence is decreasing.
n = number of the term you are looking for
1st term = 1st number in the sequence, in this case, 16
common difference = difference between one number to the next
f(n) = 16 - 1(n-1)
Assuming we are looking for the 5th term.
f(5) = 16 - 1(5-1)
= 16 - 1(4)
= 16 - 4
= 12 * as you can see, 12 is the 5th term of the sequence.
If you are looking for the equivalent of the nth term, simply substitute n by the number you are looking for and solve the equation.